Long live agrobiodiversity! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Incentive measures for sustainable use and conservation of agrobiodiversity. Experience and lessons from southern Africa. Proceedings of a workshop, Lusaka, Zambia, 11 14 September 2001. Compiled by C Almekinders, SPGRC GTZ IPGRI CTDT CTA,